Thyroid metastases from breast cancer: a case report and brief literature review - He, Siqi; Li, Jicheng; Wang, Donglai; Nong, Qiaohong; Li, Guangxin; Yin, Ying; Liu, Xiaoling (Frontiers in Oncology, 2025)
Thyroid metastasis from breast cancer is a rare occurrence and often indicates a poor prognosis. We report the case of a young female patient with thyroid metastasis from breast cancer after being diagnosed with the Graves’ disease, and review the clinical characteristics and diagnostic approach of thyroid metastases. The mechanism may be associated with altered microenvironment induced by the Graves’ disease and Hashimoto’s thyroiditis. Thyroid function and abnormal imaging examination should be paid attention during breast cancer patients’ follow-up. Early identification and individualized treatment of thyroid metastasis may contribute to prolonged survival and improved quality of life.